Protamine cleavage specificity of the avian pathogen Escherichia coli OmpT reveals two substrate-binding sites related to virulence - Liu, Juanhua; Jiang, Luyao; Wang, Hang; Wu, Jiayan; Gao, Qingqing; Huan, Changchao; Gao, Song (Frontiers in Veterinary Science, 2024)
The pathogenic nature of bacteria can be increased by cleaving antimicrobial peptides using omptins, to avoid or counter the host’s natural immune defenses. Plasmid-encoded OmpT (pOmpT or ArlC) in avian pathogenic Escherichia coli (APEC), like the chromosome-encoded OmpT (cOmpT), belongs to the omptin family and both exhibit highly similar sequences and structures. Through sequence alignment and physiological examinations, pOmpT has been identified as a virulence factor, distinct from cOmpT in terms of substrate specificity. When pOmpT is compared with cOmpT regarding their proteolytic activities and target substrates, Asp267 and Ser276 on loop 5 of cOmpT are found to be binding sites that facilitate substrate anchoring and enhance substrate cleavage (protamine or synthetic peptide) by the catalytic center. Conversely, the characteristics of residues at positions 267 and 276 on loop 5 of pOmpT inhibit protamine cleavage, yet allow the specific cleavage of the human antimicrobial peptide RNase 7, which plays a role in host defense. This finding suggests a relationship between these two binding sites and substrate specificity. Furthermore, the substrate-binding sites (residues 267 and 276, particularly residue 267) of cOmpT and pOmpT are determined to be critical in the virulence of APEC. In summary, residues 267 and 276 of pOmpT are crucial for the pathogenicity of APEC and offer new insights into the determinants of APEC virulence and the development of antimicrobial drugs.